Impact of PGPR inoculation on photosynthetic pigment and protein contents in Arachis hypogaea L. - G. Amalan Robert; R. Kalaikandhan, S. Mathivanan, AL. A. Chidambaram (Journal of Scientific Agriculture, 2017)
The impact of microbial consortium comprising plant development advancing rhizobacteria (PGPR) like Rhizobium, Pseudomonas and Bacillus were tried independently and in blend of Arachis hypogaea. The mixes of previously mentioned PGPR strains essentially expanded photosynthetic color (chlorophyll an and b, add up to chlorophyll and carotenoid) and protein content in A. hypogaea, when contrasted with the un-inoculated control. The consequences of this study propose that PGPR connected in mix can possibly build the photosynthetic colors and protein substance of A. hypogaea which can be a potential tool in increasing the yield in this economically important crop in sustainable way.